2017
DOI: 10.1016/j.apsusc.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

First principles study of elemental mercury (Hg0) adsorption on low index CoMnO3 surfaces

Abstract: The density functional theory (DFT) is applied to predict elemental mercury (Hg 0) adsorption on CoMnO 3 surface for the first time. GGA/PBE functional were selected to determine the potential Hg 0 capture mechanisms. The results show that Hg 0 has good affinity with CoMnO 3 surfaces with chemical adsorption. The adsorption energy of Hg 0-CoMnO 3 (1 0 0), Hg 0-CoMnO 3 (1 0 1) and Hg 0-CoMnO 3 (1 1 0) are-85.225,-72.305 and-70.729 kJ/mol, respectively. The Hg-Mn and Hg-Co mechanisms were revealed on low index s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…10−13 However, the costs of these metals as sorbents are still very high. Hence, many reports have also shown that low-cost transition metal oxides (e.g., Co 3 O 4 , 14 ZnO, 15 MnO 2 , 16−20 Fe 2 O 3 , 21 CuO, 22 CoMnO 3 , 23 and CaO 24,25 ) and spinel ferrite 26 are suitable materials for the removal of Hg 0 . To date, novel sorbent injection is still considered to be a potential and cost-effective mercury removal technology.…”
Section: Introductionmentioning
confidence: 99%
“…10−13 However, the costs of these metals as sorbents are still very high. Hence, many reports have also shown that low-cost transition metal oxides (e.g., Co 3 O 4 , 14 ZnO, 15 MnO 2 , 16−20 Fe 2 O 3 , 21 CuO, 22 CoMnO 3 , 23 and CaO 24,25 ) and spinel ferrite 26 are suitable materials for the removal of Hg 0 . To date, novel sorbent injection is still considered to be a potential and cost-effective mercury removal technology.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding adsorption energies are −0.57 and −0.61 eV, respectively, which are less than those of 1C. Additionally, many other studies ,,, also found that the surface metal sites are more active than oxygen sites for Hg 0 adsorption. All of the above analyses suggest that Hg 0 adsorption on the Co 3 O 4 catalyst is controlled by the chemisorption mechanism and the surface Co 3+ is the most active adsorption site.…”
Section: Results and Discussionmentioning
confidence: 84%
“…Fortunately, density functional theory (DFT) calculations can be used to fill this gap. Increasingly, researchers have performed DFT calculations to study Hg 0 adsorption and oxidation on different sorbents and catalysts at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…DFT calculations have provided powerful support for experimental studies on mercury chemistry through the analysis of adsorption energies, electronic geometry, charge transfer, thermodynamic properties, etc. Researchers have reported the adsorption and oxidation mechanisms of mercury species on various metals, metal oxides, carbonaceous surfaces, CaO surfaces, spinel-type MnFe 2 O 4 , perovskite-type CoMnO 3 surfaces, metal sulfide surfaces, metal--organic frameworks (MOFs), and alkali-metal-based sorbents using theoretical methods. Theoretical calculations have also been carried out to elucidate the mechanism of mercury oxidation over chlorine- and cupric-impregnated activated carbon , and on single-atom catalysts with different graphene-based substrates …”
Section: Introductionmentioning
confidence: 99%
“…11,18−20 Quantum chemical calculations, especially density functional theory (DFT), are ideally suited for evaluating heterogeneous oxidation mechanisms involved in mercury species adsorption on sorbent/catalyst surfaces at the molecular-electronic level. 41 surfaces, metal sulfide surfaces, 42 metal--organic frameworks (MOFs), 43 and alkali-metal-based sorbents 44 using theoretical methods. Theoretical calculations have also been carried out to elucidate the mechanism of mercury oxidation over chlorine-and cupric-impregnated activated carbon 45,46 and on single-atom catalysts with different graphene-based substrates.…”
Section: Introductionmentioning
confidence: 99%